Transverse Sinus Stenosis in Refractory Chronic Headache Patients: An Observational Study - Favoni, Valentina; Pierangeli, Giulia; Cirillo, Luigi; Toni, Francesco; Abu-Rumeileh, Samir; La Morgia, Chiara; Messia, Monica; Agati, Raffaele; Cortelli, Pietro; Cevoli, Sabina (Frontiers in Neurology, 2019)
Background Transverse sinus stenosis is a common brain MRI finding in chronic migraine (CM) and Chronic Tension-type Headache (CTTH) patients in clinical practice, however its clinical and diagnostic role is unclear. The aim of the study is to determine the prevalence of transverse sinus stenosis in chronic headache patients resistant to prophylactic therapies and to verify whether this is a useful finding for identifying patients with intracranial hypertension. Methods This is an observational study. Patients with refractory CM and CTTH underwent a 3T- magnetic resonance venography (MRV) before CSF opening pressure measurement. Transverse sinus stenosis was determined using the combined conduit score (CCS). Patients with opening pressure >200 repeated MRV study 1 month after CSF withdrawal to evaluate changes in neuroimaging findings. Results We analyzed MRV studies of 40 patients (32 F, 8 M; mean age 49.4±10.8; mean BMI 26.7±6.4; 39 CM and 1 CTTH with concomitant episodic migraine). Nineteen cases (47.5%) had evidence of transverse sinus stenosis: bilateral in 7 patients (17.5%); unilateral in 12 cases (30%). No statistically significant differences in transverse sinus stenosis distribution were found between patients with opening pressure <200 mmH2O and those with opening pressure >200 mmH2O. On Spearman bivariate test, there was no correlation between opening pressure and CCS score. No changes of neuroimaging findings were found 1 month after CSF withdrawal. Conclusion Transverse sinus stenosis is a frequent radiological finding (47.5%) in CM and CTTH patients refractory to preventive treatments. However, this finding is not suggestive of intracranial hypertension. Whether transverse sinus stenosis may be a possible risk factor for chronic headache or a comorbidity needs to be evaluated in larger epidemiological studies.